How do you solve (2m + 3)(4m + 3) = 0?

1 Answer
Mar 14, 2018

m=-12, -6

Explanation:

Multiply the equation using FOIL

( 2m + 3 ) ( 4m + 3 ) = 0
(2m * 4m) + (2m * 3) + (3 * 4m) + (3 * 3) = 0
8m^2 + 6m + 12m + 9 = 0
8m^2 + 18m + 9 = 0

Since it would be sort of difficult to factor mentally,
we use the quadratic equation
(or just keep plugging in factors till you get the answer)

(- b +- sqrt(b^2 - 4ac))/(2a)

(-(18) +- sqrt((18)^2 - 4(8)(9)))/(2(8))

(-18 +- sqrt(324-288))/16

(-18 +- sqrt(36))/16

(-18+-6)/16

(-9+-3)/8=0

m=-12, -6